Taxonomy of educational objectives and evaluation of learning outcomes - Aulia, Rahma Tifani; Aprianti, Emy; Larasati, Danissa; Anggraini, Dini; Putih, Anggi Agustina Merah (EDUCTUM: Journal Research, 2026)
The taxonomy of educational objectives plays a strategic role in formulating learning directions and serves as a basis for evaluating learning outcomes. The division of educational objectives into cognitive, affective, and psychomotor domains requires alignment between learning planning, the implementation of the learning process, and the evaluation techniques used. This study aims to analyze the concept of the taxonomy of educational objectives and its relevance to evaluating learning outcomes in the learning context. This study uses a qualitative approach with a literature study method. Data were obtained through a review of various literature sources in the form of educational textbooks, scientific journal articles, and relevant educational policy documents. Data analysis techniques were carried out through the stages of data reduction, data presentation, and descriptive-analytical conclusion drawing. The results show that the taxonomy of educational objectives serves as a conceptual framework that guides educators in formulating learning objectives and determining appropriate evaluation instruments. Evaluation of learning outcomes based on the taxonomy of educational objectives is able to measure learning outcomes comprehensively, not only in cognitive aspects, but also in aspects of attitudes and skills.